2022
DOI: 10.1038/s41598-022-07765-5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of bacterial diversity using 16S rRNA sequencing and prediction of its functionalities in Moroccan phosphate mine ecosystem

Abstract: Native plants in extreme environments may harbor some unique microbial communities with particular functions to sustain their growth and tolerance to harsh conditions. The aim of this study was to investigate the bacterial communities profiles in some native plants and samples of the Moroccan phosphate mine ecosystem by assessing the percentages of taxonomic identification using six hypervariable regions of the 16S rRNA. The rhizosphere of the three wild plants in the Moroccan phosphate mine is characterized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 64 publications
1
11
0
Order By: Relevance
“…Crop plants depend on the syntropic interaction with their below-ground microflora or rhizobiome, which provide resistance against an array of stressors such as drought, salinity, heavy metal pollution, and biotic stresses. Next-generation omics approaches have provided new insights into the biodiversity of soil-dwelling microbes and revealed that about 1,000 Gbp of microbial genomic content is available per gram of soil ( Vogel et al, 2009 ; Friedman and Alm, 2012 ; Azaroual et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Crop plants depend on the syntropic interaction with their below-ground microflora or rhizobiome, which provide resistance against an array of stressors such as drought, salinity, heavy metal pollution, and biotic stresses. Next-generation omics approaches have provided new insights into the biodiversity of soil-dwelling microbes and revealed that about 1,000 Gbp of microbial genomic content is available per gram of soil ( Vogel et al, 2009 ; Friedman and Alm, 2012 ; Azaroual et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the diversity of phyllospheric bacteria is vital for elucidating the possible causes of plant diseases, and these can be fully analysed from various plant hosts (Dong et al., 2019). Significant research efforts have, in the recent past, focused on studying microorganisms associated with plants, but such analysis of their composition, activities and functions has remained challenging (Azaroual et al., 2022). Traditional microbiological investigations of microbiota involve isolating and cultivating single strains, followed by morphological and biochemical characterizations.…”
Section: Introductionmentioning
confidence: 99%
“…Significant research efforts have, in the recent past, focused on studying microorganisms associated with plants, but such analysis of their composition, activities and functions has remained challenging (Azaroual et al, 2022). Traditional microbiological investigations of microbiota involve isolating and cultivating single strains, followed by morphological and biochemical characterizations.…”
mentioning
confidence: 99%
“…Phytostabilization process can be improved with the use of microorganisms with the ability to degrade contaminants and/or with the ability to promote plant growth (PGPB, plant growth promoting bacteria) under stress conditions ( Kuiper et al, 2004 ; Azaroual et al, 2022 ). Traditionally, PGPB were used primarily to help plants absorb nutrients from the environment or to prevent plant diseases, in both cases by promoting their development.…”
Section: Introductionmentioning
confidence: 99%